Clinical and Genetic Study of Algerian Patients with Spinal Muscular Atrophy. (24th March 2013) - Sifi, Y.; Sifi, K.; Boulefkhad, A.; Abadi, N.; Bouderda, Z.; Cheriet, R.; Magen, M.; Bonnefont, J. P.; Munnich, A.; Benlatreche, C.; Hamri, A.
Abstract : Spinal muscular atrophy ( SMA ) is the second most common lethal autosomal recessive disorder. It is divided into the acute Werdnig-Hoffmann disease (type I), the intermediate form (type II), the Kugelberg-Welander disease (type III), and the adult form (type IV). The gene involved in all four forms of SMA, the so-called survival motor neuron ( SMN ) gene, is duplicated, with a telomeric (tel SMN or SMN 1) and a centromeric copy (cent SMN or SMN 2). SMN 1 is homozygously deleted in over 95% of SMA patients. Another candidate gene in SMA is the neuronal apoptosis inhibitory protein ( NAIP ) gene; it shows homozygous deletions in 45–67% of type I and 20–42% of type II/type III patients. Here we studied the SMN and NAIP genes in 92 Algerian SMA patients (20 type I, 16 type II, 53 type III, and 3 type IV) from 57 unrelated families, using a semiquantitative PCR approach. Homozygous deletions of SMN 1 exons 7 and/or 8 were found in 75% of the families. Deletions of exon 4 and/or 5 of the NAIP gene were found in around 25%. Conversely, the quantitative analysis of SMN 2 copies showed a significant correlation between SMN 2 copy number and the type of SMA .